Building a Web-Based Application for Transaction Recording and Inventory Management at Unipro Store - Peter, Peter; Mulyawan, Bagus (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2024)
Unipro Store, a retail shop specializing in cellphone accessories, faces significant challenges in recording transactions and managing inventory due to its reliance on manual processes. All transactions, whether purchases from suppliers or sales conducted through various channels such as WhatsApp, Tokopedia, Shopee, or in-store are still documented manually using a notebook. This manual system makes it difficult for shop owners to retrieve historical transaction data and increases the risk of data loss, as there is no backup if the notebook is lost or damaged. To address these issues, a transaction recording and inventory management application has been designed to streamline the management of product stock, sales, and purchase data. The application supports two types of users: the owner and the admin. Its development follows the Software Development Life Cycle (SDLC) using the waterfall model. During implementation, HTML, CSS, and JavaScript were utilized alongside the Bootstrap and ASP.NET frameworks to develop the application, with Microsoft SQL Server selected as the database solution. In the testing phase, user acceptance testing (UAT) was conducted using a black box testing approach, successfully passing all test scenarios. Additionally, a System Usability Scale (SUS) questionnaire was distributed, yielding a final score of 81.67, which falls under grade A in the usability assessment.